Nota Técnica: Reply to a particle physicist (Respuesta a un físico de partículas) - Gall, C. A. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
This note to the editor discusses a reply made by S.L. Glashow to the author's letter concerning the proposed superconducting Super Collider (SSC), that appeared in Physics Toda, February 1986. The philosophical viewpoint of particle physicists is contrasted with that of the author. This puts in perspective the long term implication of building larger and larger particle accelerators.